Plan de mantenimiento y conservación de los equipos y materiales de un laboratorio de ciencias naturales en la Universidad Técnica De Cotopaxi año lectivo septiembre 2011 marzo 2012 - Becerra Torres, Mónica Fernanda (2013)
This Project was based on the necessity of the Cotopaxi Technical University on counting witha Natural Sciences Laboratory, in this way student of the career and others can carry out their practices. First Establishing to facilitate a laboratory and upon all to apply a maintenance and conservation plan for the Natural Sciences, and it is necessary to implement an instructions guide for the proper management of the equipment .The methods and techniques used for the investigation were: the polls and interviews, obtaining as a result that it is necessary to keep norms in the laboratory in order to prolong the useful life of the material, these standards have to be personal which are related to order, the utilization of the resources and it must be a challenge for the students to keep this valuable resource responsibly. The utilization of the Natural Sciences laboratory is compromised with the search of academic excellence, favoring investigative formative activities, and in this way to fulfill the current society needs.